1994
DOI: 10.1093/ndt/9.8.1097
|View full text |Cite
|
Sign up to set email alerts
|

Similar rate of progression in the predialysis phase in type I and type II diabetes mellitus

Abstract: Progression of diabetic nephropathy from the stage of macroproteinuria with near-normal renal function until start of dialysis was compared in 16 patients with type I and 16 patients with type II diabetes mellitus. The mean creatinine clearance at the beginning of the study was 89 +/- 13 ml/min/1.73 m2 in patients with type I and 81 +/- 6 ml/min/1.73 m2 in those with type II diabetes. Dialysis was started after a mean interval of 77 (44-133) months, when creatinine clearance had decreased to 8 +/- 2 ml/min/1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 0 publications
7
60
0
2
Order By: Relevance
“…However, arterial blood pressure was significantly higher in smokers than in nonsmokers (159/89 vs. 141/82 mmHg). Unfortunately, the levels of albuminuria were not presented (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, arterial blood pressure was significantly higher in smokers than in nonsmokers (159/89 vs. 141/82 mmHg). Unfortunately, the levels of albuminuria were not presented (24).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the above-mentioned studies are characterized by a small number of patients with overt diabetic nephropathy (20,23,24), short duration of follow-up (23), inadequate methods of urine collection (20), missing information on albuminuria (23,24), and most important, inaccurate methods of estimating the decline in kidney function using serum creatinine (20,23) or creatinine clearance (23,24). To obtain valid determination of the rate of decline in GFR, the following requirements should be fulfilled: the applied GFR method should have good accuracy and precision, repeated measurements of GFR should be performed (approximately every 6 -12 months), and the observation period should be extended to at least 2 years (25).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, smoking also increases the risk of subjects to develop type Ⅱ diabetes, possibly because it increases insulin resistance [62] . Furthermore, a growing body of evidence compared non-diabetic smokers and non-smokers and found that smokers were more insulin resistant and hyperinsulinemic [63] . Furthermore, smoking impaired insulin action, mainly due to a lowering of peripheral glucose uptake [64] ; thus, smoking is a key risk factor for the subject to develop type Ⅱ diabetes and secondary complications.…”
Section: Comradeship Between Smoking and Diabetic Nephropathy: Exacermentioning
confidence: 99%
“…The available literature documents that smoking (1) increases the risk to develop microalbuminuria (14,20 -30), (2) accelerates the rate of progression from microalbuminuria to manifest proteinuria (31)(32)(33)(34)(35)(36), and (3) accelerates progression of renal failure (32,(37)(38)(39)(40).…”
Section: Adverse Renal Effects Of Smoking In Patients With Renal Diseasementioning
confidence: 99%
“…Another prospective study investigated the progression rate in the predialysis phase. Sixteen patients with type 1 diabetes and 16 patients with type 2 diabetes were studied (37). At study-entry, all patients had near-normal renal function and overt proteinuria.…”
Section: Adverse Renal Effects Of Smoking In Patients With Renal Diseasementioning
confidence: 99%